Dietary Antibiotic Growth Promoters Down-Regulate Intestinal Inflammatory Cytokine Expression in Chickens Challenged With LPS or Co-infected With Eimeria maxima and Clostridium perfringens - Oh, Sungtaek; Lillehoj, Hyun S.; Lee, Youngsub; Bravo, David; Lillehoj, Erik P. (Frontiers in Veterinary Science, 2019)
Subtherapeutic levels of dietary antibiotics increase growth performance in domestic animals, but the mechanisms are poorly understood. Here, 1-week-old broiler chickens were challenged with LPS (experiment 1), or co-infected with Eimeria maxima and Clostridium perfringens as an experimental model of necrotic enteritis (experiment 2), and fed a standard basal diet or a basal diet supplemented with virginiamycin or bacitracin methylene disalicylate. In experiment 1, LPS-challenged chickens fed the unsupplemented diet had decreased body weight gains, compared with unsupplemented controls given the PBS control. In contrast, antibiotic supplementation increased body weight gains in both the LPS-challenged and PBS groups, compared with the antibiotic-free diet. LPS-challenged chickens fed the unsupplemented diet had increased expression levels of intestinal tight junction proteins (ZO1, JAM2), MUC2 gel-forming mucin, and inflammatory cytokines (IL-1β, IL-2, IL-6, IL-8, IL-17A) at 24 hr post-challenge, compared with unsupplemented chickens given the PBS control. However, LPS-challenged chickens fed the antibiotic-supplemented diets had decreased levels of intestinal inflammatory cytokine transcripts, compared with LPS-challenged chickens given the unsupplemented basal diet. In experiment 2, E. maxima/C. perfringens-co-infected chickens fed the antibiotic-supplemented diets had increased body weight gains, decreased intestinal pathology, and greater intestinal crypt depth, compared with co-infected chickens given the unsupplemented diet. Further, similar to LPS challenge, E. maxima/C. perfringens-co-infection of chickens fed the antibiotic-supplemented diets decreased expression levels of intestinal inflammatory cytokines, compared with co-infected chickens given the unsupplemented diet. These results support the hypothesis that dietary antibiotic growth promoters might increase poultry growth, in part, through down-regulation of pathogen-induced inflammatory responses.